Solar photocatalytic degradation of ibuprofen with a magnetic catalyst: Effects of parameters, efficiency in effluent, mechanism and toxicity evolution. (1st May 2021) - Gong, Han; Chu, Wei; Huang, Yumei; Xu, Lijie; Chen, Meijuan; Yan, Muting
Abstract: The environmental-friendly photocatalytic process with a magnetic catalyst CoFe2 O4 /TiO2 mediated by solar light for ibuprofen (IBP) degradation in pure water, wastewater effluent and artificial seawater was investigated systematically. The study aims to reveal the efficiency, the mechanism and toxicity evolution during IBP degradation. Hydroxyl radicals and photo-hole (h + ) were found to contribute to the IBP decay. The presence of SO4 2− showed no significant effect, while NO3 − accelerated the photodegradation, and other anions including HCO3 −, Cl −, F −, and Br − showed significant inhibition. The removal efficiency was significantly elevated with the addition of peroxymonosulfate (PMS) or persulfate (PS) ([Oxidant]0 :[IBP]0 = 0.4–4), with reaction rate of 5.3–13.1 and 1.3–2.9 times as high as the control group, respectively. However, the reaction was slowed down with the introduction of H2 O2 . A mathematic model was employed to describe the effect of ferrate, high concentration or stepwise addition of ferrate was suggested to play a positive role in IBP photodegradation. Thirteen transformation products were identified and five of them were newly reported. The degradation pathways including hydroxylation, the benzene ring opening and the oxidation of carbon were proposed. IBP can be efficiently removed when spiked in wastewater and seawater despite the decreased degradation rate by 41% and 56%, respectively. Compared to the IBP removal, mineralization was relatively lower. The adverse effect of the parent compound IBP to the green algae Chlorella vulgaris was gradually eliminated with the decomposition of IBP. The transformation product C178a which possibly posed toxicity to rotifers Brachionus calyciflorus can also be efficiently removed, indicating that the photocatalysis process is effective in IBP removal, mineralization and toxicity elimination. Graphical abstract: Image 1 Highlights: OH. and photo-hole contributed to photocatalytic degradation of ibuprofen Four commonly used oxidants showed different impacts on ibuprofen photodegradation. The process is efficient in treatment and mineralization of effluent and seawater. Three dominant pathways were proposed as mechanisms of ibuprofen degradation. A potential toxic product was detected and removed by the treatment process. Abstract : The photocatalytic process mediated by solar light is efficient for IBP removal in wastewater effluent and artificial seawater, mineralization and toxicity elimination.